Building capability for clinician-led genomic change: insights from use and non-use of a theory-informed model for change - Martyn, Melissa; Clarke, Amy; Do, Trang; Dawson-McClaren, Belinda; Gaff, Clara (Frontiers in Genetics, 2025)
Genomics is relevant to the practice of diverse medical specialties. However, integrating genomics into these specialties requires complex interventions to promote adoption by clinicians and organizational (service and hospital) re-design. Clinicians wanting to “champion” use of genomics rarely have experience in leading complex interventions. A practical evidence- and theory-informed model for change (M4C) designed for clinicians could increase likelihood of success of clinician-led complex practice change interventions. No such model could be identified, so we drew on three existing frameworks which collectively met our selection criteria to develop one. A case study approach was chosen to understand use of the M4C by clinicians leading three clinical change projects across hospitals. Informed by the COM-B system, we provided a toolkit and expert coaching to support use of the M4C. Mixed-methods data was collected: toolkit access; review of expert team notes; evaluation reports; focus groups and interviews. Coaching in all aspects of the M4C was provided, with clinicians particularly valuing coaching in action research and community engagement. Despite theoretical alignment of our strategies to promote adoption of the M4C, only 5/37 team members accessed the toolkit. Although clinicians did not independently engage with the M4C, they did embrace the concepts within it through coaching, with the expert team noting behavior change e.g., in engagement, leading to changes in project implementation. Access to expert support embedded within organizational (hospital) structures is needed to support clinicians to lead the system re-design required to incorporate innovations like genomics in healthcare.